A short-cut method for computing positive variance component estimates - Joachim Hartung (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 1999)
In a general variance component model with positive variance components a short-cut method is presented that yields almost everywhere for these components positive estimators that are invariant with respect to mean value translation and stay near the unbiasedness. – – In einem allgemeinen Varianz-Komponenten-Modell mit positiven Varianzkomponenten wird eine verkürzte Methode vorgestellt, welche für diese Komponenten fast überall positive Schätzer ergibt, die invariant bzgl. Mittelwerttranslationen sind und nahe der Unverzerrtheit bleiben.
Keywords: 519; Variance components; Minque; positive Minque; Invariance; approximate unbiased positive variance estimates